Guerilla project management - Hanley, Kenneth T. (Vienna, VA : Management Concepts, 2011)
The book emphasizes key project management competencies, including managing stakeholders effectively, assessing risk accurately, and getting agreement on the objective measures of project success.
Includes bibliographical references and index.
rua 25/10/13
Loans
Keywords: Project management